YIELD AND YIELD COMPONENTS OF SOYBEAN [GLYCINE MAX (L.) MERRILL] AS INFLUENCED BY VARIETY AND PLANT SPACING IN THE SUDAN SAVANNA OF BAUCHI STATE, NIGERIA - Samaila, A.; Mubarak, M. U.; Abdulrahman, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted during the 2025 rainy season at Yayu District, Katagum Local Government Area (LGA), Bauchi State to study the yield and yield components of soybean as influenced by variety and plant spacing. The treatments consisted of Five (5) soybean varieties (TGx1951-3F, TGx1835-10E, TGx1987-62F, TGx1904-6F and Samsoy-2) and three (3) intra-row spacings (20 × 20 cm (S1; 250,000 plants ha⁻¹), 30 × 30 cm (S2; 111,111 plants ha⁻¹) and 45 × 45 cm (S3; 49,383 plants ha⁻¹). These were factorially combined to give 15 treatments and laid out in a Randomised Complete Block Design (RCBD) replicated four times. Data were collected on grain yield (kg ha⁻¹), number of pods per plant, 100-seed weight (g) and harvest index (%). All data collected were subjected to Analysis of Variance (ANOVA) and means were separated using Fisher’s Least Significant Difference (LSD) at 5% probability level. Result of the experiment revealed a significant (P ≤ 0.01) difference among the parameters observed. The result further indicated that, Variety TGx1951-3F achieved the highest grain yield of 1865 kg ha⁻¹, while the 30 × 30 cm spacing proved to be the best spacing with the yield of 1929 kg ha⁻¹ across all the varieties. The interaction of TGx1951-3F × 30 × 30 cm gave the peak cell mean of 2246 kg ha⁻¹. Based on the result of this findings, TGx1951-3F at a spacing of 30 × 30 cm is recommended for immediate adoption by soybean farmers in the study area.